2002
DOI: 10.1002/path.1159
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac stem cells

Abstract: Augmentation of myocardial performance in experimental models of therapeutic infarction and heart failure has been achieved by the transplantation of exogenous cells into damaged myocardium, a procedure known as cellular cardiomyoplasty (CCM). Historically, a wide range of cell types have been used for CCM, including rat and human fetal ventricular myocytes, but the availability of human fetal donor cells for clinical purposes is limited. The quest for suitable alternative donor cells has prompted research int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2002
2002
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 109 publications
(185 reference statements)
0
38
0
3
Order By: Relevance
“…A novel and exciting potential methodology to reverse myocardial remodeling associated with myocardial infarction [46] is regeneration of myocardium using bone marrow (BM)-derived mesenchymal cells, endothelial progenitor cells and endogenous cells [47][48][49][50]. Given its essential role in BM homing and recruitment [49,51], CXCL12 is a candidate to promote stem cells recruitment to the heart. Because CXCR4 may negatively impact myocardial function, strategies [52] that primarily employ up-regulation of CXCL12 may need to be examined more closely.…”
Section: Discussionmentioning
confidence: 99%
“…A novel and exciting potential methodology to reverse myocardial remodeling associated with myocardial infarction [46] is regeneration of myocardium using bone marrow (BM)-derived mesenchymal cells, endothelial progenitor cells and endogenous cells [47][48][49][50]. Given its essential role in BM homing and recruitment [49,51], CXCL12 is a candidate to promote stem cells recruitment to the heart. Because CXCR4 may negatively impact myocardial function, strategies [52] that primarily employ up-regulation of CXCL12 may need to be examined more closely.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate a significant contribution of stem cells, likely of bone marrow origin, to the homeostasis and/or repair of the adult heart (Jackson et al, 2001;Orlic et al, 2001;Hughes, 2002;Laflamme et al, 2002;Quaini et al, 2002). In addition, the existence of a socalled myocardial stem cell population has been suggested (Hierlihy et al, 2002), but it is not clear how this population contributes to the respective established cardiac cell types in the heart, nor has the origin/phenotype of these cells been properly described.…”
Section: Contributions Of Stem Cells To the Adult Heartmentioning
confidence: 99%
“…[7][8][9][10] Cellular cardiomyoplasty, a procedure involving the transplantation of exogenous cells into the heart, is a possible approach by which to regenerate diseased myocardium, deliver therapeutic genes, and improve cardiac function. 11 Researchers have investigated the use of various cell types for cardiac repair, including cardiomyocytes, fibroblasts, embryonic stem cells, endothelial progenitor cells, bone marrow-derived cells, hematopoietic stem cells, mesenchymal stem cells, smooth muscle cells, skeletal muscle-derived cells, 12 and the recently identified cardiac stem cells. [13][14][15][16][17] Notably, numerous research groups have found that skeletal muscle-derived cells can successfully engraft in the heart and improve cardiac performance in animal models.…”
Section: Introductionmentioning
confidence: 99%